2013
DOI: 10.7554/elife.00750
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of frequency modulated transcription in single cells using light activation

Abstract: Single-cell analysis has revealed that transcription is dynamic and stochastic, but tools are lacking that can determine the mechanism operating at a single gene. Here we utilize single-molecule observations of RNA in fixed and living cells to develop a single-cell model of steroid-receptor mediated gene activation. We determine that steroids drive mRNA synthesis by frequency modulation of transcription. This digital behavior in single cells gives rise to the well-known analog dose response across the populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
166
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(188 citation statements)
references
References 67 publications
20
166
0
Order By: Relevance
“…However, there has been few studies observing the correlation between an upstream transcription activation and a downstream transcription rate (Larson, 2011). In a recent study, Larson et al (2013) developed a single molecule approach for measuring the dynamical transcription activity of genes responsive to the activation of steroid-receptors. They demonstrated how the ensemble steroid dose response arises from the stochastic behavior of individual genes.…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been few studies observing the correlation between an upstream transcription activation and a downstream transcription rate (Larson, 2011). In a recent study, Larson et al (2013) developed a single molecule approach for measuring the dynamical transcription activity of genes responsive to the activation of steroid-receptors. They demonstrated how the ensemble steroid dose response arises from the stochastic behavior of individual genes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the timing and coordination of these interactions remained elusive. Initial biochemical characterization suggested that transcription initiation may take 30 min to 1 h in vitro (Hawley and Roeder 1987), and similar or longer time scales hold true for transcription initiation in the cell as measured by the latest single-molecule imaging-based technologies (Larson et al 2013). On the other hand, much shorter residence times have been reported for gene-specific activators (Chen et al 2014) and the GTF TFIIB in living cells (Chen et al 2002).…”
mentioning
confidence: 99%
“…Burst size, that is, the number of transcripts per burst, and burst frequency, that is, the number of transcriptional bursts per time unit are gene specific and appear to depend on the promoter architecture, such as the presence of a CAAT box, a TATA box, the size of the nucleosome-free region as well as the location and number of transcription factor binding sites [7][8][9][10][11][12] . Burst sizes of between 1 and 450 transcripts per burst have been observed followed by periods of inactivity of up to several hours 7,8,[12][13][14][15][16][17][18][19] .…”
mentioning
confidence: 99%